2018
DOI: 10.1093/ibd/izy126
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TNF Therapy Induces CD4+ T-Cell Production of IL-22 and Promotes Epithelial Repairs in Patients With Crohn’s Disease

Abstract: Our results uncover a novel mechanism whereby anti-TNF therapy upregulates IL-22 production in CD patients through promoting Th22 cell differentiation and contributes to intestinal epithelial barrier repairs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 38 publications
1
43
0
Order By: Relevance
“…Similar to the beneficial role of Tregs in mucosal immunity, the Th22 subset of CD4+ T-cells has been shown to promote homeostasis. In this regard, IL-22 produced by these cells induces the expression of tight junction proteins (i.e., claudin 1 and ZO-1) in epithelial cells, thus increasing the integrity of the mucosal epithelial barrier and protecting it from inflammation (54). Accordingly, it has been shown that the administration of anti-TNF-α therapy (infliximab) in CD patients, which ameliorates gut inflammation, upregulates IL-22 production contributing to intestinal epithelial barrier repair (54).…”
Section: T-cell Driven Inflammation Plays a Fundamental Role In The Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the beneficial role of Tregs in mucosal immunity, the Th22 subset of CD4+ T-cells has been shown to promote homeostasis. In this regard, IL-22 produced by these cells induces the expression of tight junction proteins (i.e., claudin 1 and ZO-1) in epithelial cells, thus increasing the integrity of the mucosal epithelial barrier and protecting it from inflammation (54). Accordingly, it has been shown that the administration of anti-TNF-α therapy (infliximab) in CD patients, which ameliorates gut inflammation, upregulates IL-22 production contributing to intestinal epithelial barrier repair (54).…”
Section: T-cell Driven Inflammation Plays a Fundamental Role In The Pmentioning
confidence: 99%
“…In this regard, IL-22 produced by these cells induces the expression of tight junction proteins (i.e., claudin 1 and ZO-1) in epithelial cells, thus increasing the integrity of the mucosal epithelial barrier and protecting it from inflammation (54). Accordingly, it has been shown that the administration of anti-TNF-α therapy (infliximab) in CD patients, which ameliorates gut inflammation, upregulates IL-22 production contributing to intestinal epithelial barrier repair (54). Regarding the antigens recognised by the adaptive immune system in IBD, several autoantigens and microbiota-derived antigens have been described in both CD and UC (55, 56).…”
Section: T-cell Driven Inflammation Plays a Fundamental Role In The Pmentioning
confidence: 99%
“…Based on murine colitis models it is anticipated that high levels of IL22BP promote inflammation by inference of IL-22 mediated mucosal healing [212]. In agreement, upon response to anti-TNF-α therapy intestinal CD4 + T-cells isolated from IBD patients exhibit reduced amounts of IL-22BP expression but still express IL-22 [212], and may even up-regulate IL-22 production [215].…”
Section: Does the Il-22-il-22bp Pathway Contribute To Disease Pathology?mentioning
confidence: 93%
“…129 Homozygous deletion of IL-17A reduced enthesitis severity, while neutralization of IL-22 reduced enthesitis but exacerbated ileitis, 147 perhaps due to the well-accepted ability of IL-22 to reenforce mucosal barrier integrity. 190,191 It is remarkable that this SKG model and TNF transgenic models exhibit both experimental terminal ileitis and enthesitis in the same model systems in two different strains with two major cytokines that are therapeutic targets in SpA-and enthesitis-related disease.…”
Section: Skg Modelmentioning
confidence: 98%